Studi Analisis Audit Energi Untuk Konservasi Serta Efisiensi Listrik Gedung Unisla dengan Pendekatan Metode MCDM – Promethee - Zainal Abidin; Aynin Churlillah D (Universitas Islam Lamongan, 2018)
In Islamic University of Lamongan (UNISLA), the use of electric energy is very important because there manyactivities in UNISLA it requires a lot of electrical energy and it can cause the waste of electrical energy.To overcome this, the need for a conservation and efficiency of electrical energy is needed. In this case, it is conducting an electrical energy audit. In this research, electrical energy auditing is done at Islamic University of Lamongan precisely in Building B and Building C. From the calculation of energy audit, it can be obtained the scoreof Energy Consumption Intensity (IKE) electricity at Building B is equal to 21,28 Kwh/m2/year and at Building C is 37.59 Kwh/m2/year. From these calculations, when compared to the standards set by the government, the IKE score is included in the category of quite efficient. But the researcher wants an effort to save electricity. The saving opportunities are changes in the SOP ofbuilding facilities, the adjustment of energy-efficient building design, the application of energy-saving technologies, and the development of optimal human resources. In this research,the saving effort can be done using MCDM-Promethee method. It is a method that can make an alternative rank according to the criteria obtained where every criteria is calculated using Analytical Network Processor. (ANP) method. These criteria include economy, work culture, occupant comfort, the influence of technology application, and the sense of owning of the building.From the ranking results can be obtained that the alternative saving efforts in Building B and Building C of Lamongan Islamic University is a change SOP (Standard Operating Procedure) building facilities.